Pengaruh Kelas Sosial, Gaya Hidup Dan Kualitas Produk Terhadap Keputusan Pemebelian Di Rocket Chicken Cokroaminoto Kota Probolinggo - Maisaroh, Ida; Hendra, Joni; Tumini, Tumini (Universitas Panca Marga, 2024)
This research was conducted at Rocket Chicken Cokroaminoto, Probolinggo City, which aims to determine the impact of social class, lifestyle and product quality on purchasing decisions at Rocket Chicken Cokroaminoto, Probolinggo City. Population used by consumers who made purchases in October 2023 at Rocket Chicken Cokroaminoto, Probolinggo City. The sample in this study used a simple random sampling technique, totaling 80 Rocket Chicken Cokroaminoto consumers, Probolinggo City. The data analysis technique used is SPSS (statistical package for the social sciences) through multiple linear analysis calculation tools. The results of this research show: (1) Social class, lifestyle and product quality variables have a positive and significant influence on purchasing decisions, (2) Product quality variables have a dominant influence on purchasing decisions.